Théorie poétique, vérité et représentation du divin chez Empédocle et Pindare - Xavier Gheerbrant (Pallas, 2018)
Empedocles understands the truth-value of lyric poetry as a form of mythical authority from which the lyric poets wished to distinguish themselves; as the nature of their conception of truth depends on the necessity of honoring an athlete, the lyric poets cannot reach true knowledge about the world or about gods. Whereas Empedocles defines a scheme of vertical inspiration where the poet receives a divine discourse that he transmits to men, Pindar constructs a triangulation between the gods, the athlete, and the poet himself. Empedocles intends to criticize anthropomorphic representations of the gods in particular: he reactivates the criticisms raised by Xenophanes towards the gods in Homer and Hesiod, while giving them a new basis in terms of the theory of poetic composition.